Aluminum alloy database - Kaufman, J. G. 1931- (Knovel, 2004)
The Knovel Aluminum Database is a comprehensive summary of the chemical, mechanical, and physical properties of both wrought and cast aluminum alloys including a wide variety of types of cast aluminum alloys. The values are "typical, " as used in aluminum industry publications, to represent the average or mean and not any statistically calculated values intended for design. Among the properties included are: Nominal Chemical Compositions and Composition Limits, Density and Specific Gravity, Average Coefficient of Thermal Expansion, Melting Range, Thermal and Electrical Conductivity, Electrical Resistivity, Specific Heat, Poisson's Ratio, Coefficient of Friction, Ultimate Tensile Strength, Tensile Yield Strength, Elongation, Brinell Hardness Number, Ultimate Shear Strength, and Modulus of Elasticity. Some fatigue and toughness property indices are also included.